Inflammatory Smooth Muscle Cells Induce Endothelial Cell Alterations to Influence Cerebral Aneurysm Progression via Regulation of Integrin and VEGF Expression. Issue 6 (June 2019) - Liu, Peixi; Shi, Yuan; Fan, Zhiyuan; Zhou, Yingjie; Song, Yaying; Liu, Yingjun; Yu, Guo; An, Qingzhu; Zhu, Wei
Cerebral aneurysm growth is characterized by vessel wall frailness, although the underlying cellular mechanisms are unclear. Here, we examined the relationship between inflammatory smooth muscle cells (SMCs) and endothelial cells (ECs) in cerebral aneurysms, including the mechanisms underlying inflammatory SMC-induced changes in ECs. Five saccular cerebral aneurysms were collected and five temporal artery samples were used as controls. Cells and cytokines were detected by immunohistochemistry and TUNEL (transferase dUTP nick end labeling) assays performed to evaluate apoptosis. Human umbilical vein endothelial cells (HUVECs) were seeded on collagen I, IV, and VI-coated plates for cell adhesion assays and inflammatory SMCs (iSMCs) were established by culture in flexible silicone chambers subjected to cyclic mechanical stretch. HUVECs were cultured in iSMC-conditioned medium, followed by evaluation of their viability, apoptosis, and function, and determination of VEGF (vascular endothelial growth factor) -A and integrin levels by western blotting. Aneurysm tissue contained fewer SMCs and lacked ECs. In aneurysm walls, more matrix metalloproteinase (MMP) -1, MMP-3, and apoptotic cells were detected, accompanied by decreased collagen IV and VI levels. Cell adhesion assays revealed that more HUVECs were attached in collagen IV and VI-coated plates compared with controls. iSMC-conditioned medium significantly reduced HUVEC viability and apoptosis showed an increased trend; however, the difference was not significant. iSMC medium also reduced tube formation and migration of HUVECs. Moreover, iSMC medium reduced HUVEC expression of VEGF-A, integrin α1, integrin α2, and integrin β. Our data demonstrate a lack of SMCs and ECs in aneurysm walls, accompanied by elevated MMP and decreased collagen levels. In vitro assays showed that iSMCs induced reduction in EC adhesion, and caused EC dysfunction. Understanding of the relationships among SMC, EC, and collagens during aneurysm progression provides an additional therapeutic option for prevention of cerebral aneurysm progression.